« Il a cueilli une rose blanche pour mettre dans son carnet vide... »L’album face à la question du temps - Euriell Gobbé-Mévellec (Strenae)
The multiplicity and complexity of strategies employed by the picture book to capture time through images reveal that the question of its representation is crucial, undoubtedly because it is, for young readers, a notion to be constructed, and because the picture book plays an essential role in this learning. But capturing time through an image, beyond the initiation of the reader to this complex notion, is also a means to making the very nature of the picture book readable, to exhibiting its inner workings. Three picture books will be analyzed from this perspective in the following study, three "manifesto" picture books, in a way, that play with the definitions of the picture book: L'Heure vide, by Anne Herbauts (2000), En une seconde, by Silvio Freytes and Flavio Morais (2009), and Ligne 135, by Germano Zullo and Albertine (2012).